PERALIHAN HAK ATAS TANAH YANG TIDAK DIKETAHUI KEBERADAAN PEMILIKNYA - DIANA LUBIS (Magister Kenotariatan, Universitas Jambi, 2021)
ABSTRACT Land is one of sources of livelihood and subsistence for individuals and society so that it becomes basic needs of human beings. The urgency of land for humans’ life is appreciated by Government of the Republic of Indonesia through land national policy by the issuance of Law Number 5/1960 on the Basic Agrarian Regulations. BPN (the National Land Office) is specifically obliged to provide legal certainty to land management for citizens with various types of ownership rights to be properly used. In order to avoid any kinds of disputes, the society has to firstly understand whether the land has already had an owner, is abandoned or is still owned by the State. The research problems are how about the criteria of land that can be owned by society, how about the transfer of land title whose owner is unknown, and what role is played by the Government concerning land title transfer whose owner is unknown.This is a normative juridical research with normative juridical approach. Circumstances are not present and the legal consequences according to Indonesian Civil Law, Unknown condition of a person can lead to various problems including which will affect the legal status of that person, his wealth and marriage. This is the case with land owned by someone who is declared missing or absent (Afwezigheid) require ruling on death notification issued by a Judge; thus, all heirs who, pursuant to the laws, are rightful to transfer all authorities over their properties, are suggested to organize inherited wealth and property. Keywords: Title Transfer, Land, Owners’ Existence.